The Effects of Super Ovulation on the Number of Corpus Luteum of Coastal Sumatera Cows (Bos sumatranensis) - Depison, Depison; Adriani, Adriani; Rosadi, B (ANIMAL PRODUCTION, 2011)
The objective of this study was to observe the effects of super ovulation treatments on the number of ovulated corpus luteum. Metode   yang digunakan dalam penelitian adalah metode eksperimen. The method used in this study was experimental. Sapi-sapi diprogram untuk sinkronisasi estrus menggunakan PGF2ά. The cows were programmed to experience estrous at relatively the same time (estrous synchronization) using PGF2ά. Sapi-sapi tersebut kemudian dibagi secara acak menjadi empat perlakuan, masing-masing terdiri dari empat ekor sebagai ulangan. Data yang dihimpun dalam penelitian ini adalah jumlah corpus luteum, dan jumlah folikel tetap. Cows were divided randomly into four treatments, each of which consisting of four heads. The number of corpus luteum and the settled follicles was collected during the study. Data dianalisis menggunakan Rancangan Bujur Sangkar Latin, jika perlakuan berpengaruh nyata maka dilajutkan dengan uji lanjut Duncan. Data were analyzed using a Latin Square design. In case there was a significant difference, Duncan test was used thereafter. Result showed that Hasil penelitian menunjukkan bahwa penggunaan PGF2ά dalam pelaksanaan sinkronisasi estrus berjalan cukup baik.Hasil penelitian ini menunjukkan bahwa perlakuan superovulasi berpangaruh nyata terhadap Corpus Luteum dan folikel menetap.super ovulation had a significant effect on corpus luteum and settled follicles. Kesimpulan penelitian ini  protokol terbaik superovulasi tahun pertama adalah T-3 karena menghasilkan Corpus luteum dan Embrio yang lebih banyak.In conclusion, the best super ovulation protocol in the first year was the combination of 4 day daily injection of 40 mg of FSH in decreasing dose plus 250 µg of GnRH given at the time of estrous, because it was able to yield greater number of corpus luteum and embryos. (Animal Production 13 (1):52-56 (2011)Key Words: corpus luteum, follicle, super ovulation, Coastal Sumatera Cow